(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Nine commercial cultivars of okra were evaluated for a number of agro-botanical traits. The analysis of variance for all the traits showed highly significant variations among the genotypes. The phenotypic coefficient of variation (PCV) was found higher than the genotypic coefficient of variation (GCV) for all characters. Maximum GCV and PCV were observed for branches/plant (42.54 and 42.60) and leaves/plant (27.93 and 27.99) respectively. Heritability as well as genetic advance was found maximum for branches/plant recorded as 99.72 and 87.50 respectively. Based on D2 statistics 9 genotypes were grouped into 4 clusters, namely cluster I, II, III and IV. Highest inter-cluster distance (1.18) was observed between cluster II and cluster IV. The genotypes of cluster IV possessed heterogeneous nature and showed highest intra-cluster distance (0.65). Titanic-1, BARI Derosh-1 and Green Finger genotypes were found superior to the rest of the genotypes due to their highest cluster mean for yield/plant (955.8g), plant height (208cm), leaves/plant (60.8) and fruits/plant (31.4). These information could be useful in recombination breeding programme. Jahangirnagar University J. Biol. Sci. 3(2): 25-32, 2014 (December)